2016
DOI: 10.1089/pho.2016.4103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Conditions of Titanium Dental Implants on Bacterial Adhesion

Abstract: Laser debridement could be a useful cleaning method for peri-implantitis therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 27 publications
7
40
1
2
Order By: Relevance
“…The publication dates ranged from 1992 to 2017. Seven out of the 11 studies in this category were also presented in Section 3.4.1 . Results regarding cleaning efficacy were consistent, and all of the 11 studies reported that AA was superior to other decontamination methods or at least performed similarly to them.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…The publication dates ranged from 1992 to 2017. Seven out of the 11 studies in this category were also presented in Section 3.4.1 . Results regarding cleaning efficacy were consistent, and all of the 11 studies reported that AA was superior to other decontamination methods or at least performed similarly to them.…”
Section: Resultsmentioning
confidence: 84%
“…Compared with the nonmechanical laser decontamination, two studies reported Er: YAG laser and CO 2 laser were superior to AA in terms of keeping the surface intact. However, two other studies reported no distinct advantage of Er: YAG laser over AA, and one study even considered AA slightly superior…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations